Investigating the effectiveness and efficiency of forensic pathology practice in Western Cape, South Africa - De Jong, Jacqui Anne (Division of Forensic Medicine and Toxicology, 2017)
Introduction: In South Africa (SA), the forensic sector faces significant challenges including how to meet increasing public expectations for high quality, reliable and valid scientific and medico legal results, whilst dealing with increasing caseloads and restricted resources in a developing country. Internationally, lean six-sigma and/or business-based frameworks have been developed to define, measure and analyse the efficiency, effectiveness and output of forensic laboratories, so as to assess performance to meet such challenges. Aim: This pilot project aimed to investigate the effectiveness and efficiency of forensic pathology practice at Salt River Mortuary (SRM) by applying lean six sigma principles (define, measure, analyse and improve) and FORESIGHT metric analyses to retrospective case and staffing data, as well as prospective observational analyses. Methods: A retrospective analysis of cases admitted to Salt River Mortuary in 2015 was conducted to define and measure a snapshot of forensic pathology practice in Cape Town. In addition, observations of autopsy processes were conducted to identify bottlenecks in the system and provide suggestions for improvement. Results: An analysis of post-mortem report turn-around for 3567 cases admitted to SRM in 2015 showed that approximately 10% of cases were closed (cause of death was determined) on the day of the post-mortem, 65% within 14 days and 80% closed within a 30 day period. Certain requested ancillary investigations delayed the finalisation of cause of death; for example, only 8.33% of carbon monoxide testing and 30.31% of histological examinations were completed within the year. A process map outlining autopsy practices at SRM was generated through observational data, which also identified key bottlenecks in the process (e.g.: equipment issues). Preliminary financial data suggested that it cost on average R16 155.03 per case. Staff data demonstrated a lack of pathologists compared to other staff categories and high case load requirements. Discussion: This pilot study investigates the utilization of metrics and strategic frameworks to assess forensic pathology processes in Cape Town. This study offers a cross-sectional insight into financial performance, efficiency and effectiveness of post-mortem investigations at SRM, highlighting bottlenecks and inefficiencies, and providing suggestions for improvement. The findings will assist in forming a basis for future work into the development of a framework for monitoring performance and progress, and developing benchmark standards for the death investigation system in South Africa